Oleoresin Capsicum Spray and TASERs: A Comparison of Factors Predicting Use and Effectiveness - Brandl, Steven G.; Stroshine, Meghan S. (Criminal justice policy review, 2017)
In the last few decades, several less lethal forms of force have been introduced, adopted, and deployed by police agencies. Oleoresin capsicum (OC) spray is now used in nearly every department across the United States; the Thomas A. Swift Electric Rifle (TASER) is used in the majority of police departments. Despite their widespread use, we still know relatively little about the factors associated with the use of OC spray and TASERs and the effectiveness of these weapons in incapacitating subjects. Knowing when these weapons are used and whether they are effective would provide for a more complete understanding of their strengths and limitations and inform the debate about where less lethal weapons should be placed on use of force continua. This article contributes to the discussion by analyzing 504 use-of-force incidents where the police used OC spray or TASERs during the event. Data were obtained from a large municipal police department on incidents that occurred in 2010 and 2011. Policy considerations and directions for further research are discussed.